The role of electronic game advertisements in influencing the purchasing behavior of high school students in Al-Ahsa (The International Journal of Educational Sciences and Arts, 2024)
This study aims to understand how advertisements appearing in electronic games affect students' purchasing decisions, especially with the expansion of the use of modern technology and digital media in daily life. Electronic games are one of the platforms that witness commercial advertisements that are interactive and integrated with the game, which increases the chances of their influence on players. There is increasing interest in understanding these effects due to the prevalence of this phenomenon among students in educational stages, especially in secondary school, where students have a great ability to make consumer decisions. The results of the study indicate that the majority of students prefer to follow advertisements through various electronic games, especially those that are displayed during certain periods of play. It also showed that there is a great impact of advertisements that use exciting graphics and visual effects that attract the attention of players. The famous characters that appear in some advertisements in electronic games contribute to increasing their influence on students' behavior, as these characters serve as role models for them. The way in which advertisements are displayed, whether pop-up advertisements or in the form of integrated offers within the game, plays an important role in attracting students' attention and motivating them to make purchasing decisions. Although some students seem to be cautious about these advertisements, there is a large group of them who feel confident about the information provided by these advertisements, and show great interest in the products they offer, especially in the fields of electronic games and technical devices. Based on these results, the relationship between the increasing influence of digital advertisements on students and their purchasing decision becomes clear, which reflects the need to consider regulating these advertisements and their potential effects on purchasing behavior in the future.
Keywords: Electronic game advertisements; purchasing behavior; high school students; digital influence; Al-Ahsa; purchasing decisions